Comparative Effects of L. plantarum CGMCC 1258 and L. reuteri LR1 on Growth Performance, Antioxidant Function, and Intestinal Immunity in Weaned Pigs - Tang, Qingsong; Yi, Hongbo; Hong, Weibin; Wu, Qiwen; Yang, Xuefen; Hu, Shenglan; Xiong, Yunxia; Wang, Li; Jiang, Zongyong (Frontiers in Veterinary Science, 2021)
Lactobacillus plantarum (L. plantarum) CGMCC 1258 and Lactobacillus reuteri (L. reuteri) LR1 are two important strains of probiotics. However, their different advantages in the probiotic effect of weaned pigs are still poorly understood. Therefore, the study was to investigate the comparative effects of dietary supplementation of L. plantarum CGMCC 1258 and L. reuteri LR1 on growth performance, antioxidant function, and intestinal immunity in weaned pigs. Ninety barrows [initial body weight (BW) = 6.10 ± 0.1 kg], 21-d-old were randomly divided into 3 treatments with 5 replicates, each replicate containing 6 pigs. Pigs in control (CON) were fed a basal diet, and the basal diets supplemented with 5×1010 CFU/kg L. plantarum CGMCC 1258 (LP) or L. reuteri LR1 (LR) for 42 d, respectively. The results showed that LP increased (P < 0.05) serum superoxide dismutase (SOD), and decreased (P < 0.05) serum malondialdehyde (MDA) and the expression and secretion of interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α) and interferon-γ (IFN-γ) in intestinal mucosa, but has no significant effect on growth performance and diarrheal incidence. However, LR increased (P < 0.05) final BW and average daily gain (ADG), reduced (P < 0.05) 29 to 42 d diarrheal incidence, decreased (P < 0.05) the expression and secretion of IL-1β, IL-6, TNF-α, IFN-γ, and increased (P < 0.05) the expression of transforming growth factor-β (TGF-β) in intestinal mucosa. Additionally, the serum glutathione peroxidase (GSH-PX), mRNA relative expression of Na+-K+-2Cl- co-transporter 1 (NKCC1) and cystic fibrosis transmembrane conductance regulator (CFTR) and the content of toll-like relative (TLR2) and TLR4 in the jejunum, and secretory immunoglobulin (sIgA) content of ileal mucosa were higher (P < 0.05) than LP. Collectively, dietary L. plantarum CGMCC 1258 improved intestinal morphology, intestinal permeability, intestinal immunity and antioxidant function in weaned pigs. Dietary L. reuteri LR1 showed better growth performance, a lower incidence of diarrhea, better intestinal morphology and a higher extent of immune activation in weaned pigs.